Mismatch Profile Influences Outcome After Mechanical Thrombectomy. Issue 1 (January 2021) - Olivot, Jean-Marc; Albucher, Jean-François; Guenego, Adrien; Thalamas, Claire; Mlynash, Michael; Rousseau, Vanessa; Drif, Amel; Christensen, Soren; Sommet, Agnes; Viguier, Alain; Darcourt, Jean; Calvière, Lionel; et al.
Abstract : Background and Purpose: Mechanical thrombectomy (MT) is the recommended treatment for acute ischemic stroke caused by anterior circulation large vessel occlusion. However, despite a high rate of reperfusion, the clinical response to successful MT remains highly variable in the early time window where optimal imaging selection criteria have not been established. We hypothesize that the baseline perfusion imaging profile may help forecast the clinical response to MT in this setting. Methods: We conducted a prospective multicenter cohort study of patients with large vessel occlusion–related acute ischemic stroke treated by MT within 6 hours. Treatment decisions and the modified Rankin Scale evaluation at 3 months were performed blinded to the results of baseline perfusion imaging. Study groups were defined a posteriori based on predefined imaging profiles: target mismatch (TMM; core volume <70 mL/mismatch ratio >1.2 and mismatch volume >10 mL) versus no TMM or mismatch (MM; mismatch ratio >1.2 and volume >10 mL) versus no MM. Functional recovery (modified Rankin Scale, 0–2) at 3 months was compared based on imaging profile at baseline and whether reperfusion (modified Thrombolysis in Cerebral Infarction 2bc3) was achieved. Results: Two hundred eighteen patients (mean age, 71±15 years; median National Institutes of Health Stroke Scale score, 17 [interquartile range, 12–21]) were enrolled. Perfusion imaging profiles were 71% TMM and 82% MM. The rate of functional recovery was 54% overall. Both TMM and MM profiles were independently associated with a higher rate on functional recovery at 3 months Adjusted odds ratios were 3.3 (95% CI, 1.4–7.9) for TMM and 5.9 (95% CI, 1.8–19.6) for MM. Reperfusion (modified Thrombolysis in Cerebral Infarction 2bc3) was achieved in 86% and was more frequent in TMM and MM patients. Reperfusion was associated with a higher rate of functional recovery in MM and TMM patients but not among those with no MM. Conclusions: In this cohort study, about 80% of the patients with a large vessel occlusion–related acute ischemic stroke had evidence of penumbra, regardless of infarction volume. Perfusion imaging profiles predict the clinical response to MT. Abstract : Supplemental Digital Content is available in the text.